Impact of intrauterine administration of human chorionic gonadotropin before intrauterine insemination in infertile women: A randomized controlled trial - Leena Wadhwa; Anupama Rani (Wolters Kluwer Medknow Publications, 2021)
Background: Implantation is the rate-limiting step in the success of both intrauterine Insemination (IUI) and in vitro fertilization cycles. Numerous interventions that target various local signals have been tried to improve the implantation and clinical pregnancy rate (CPR). The most significant of these signals is human chorionic gonadotropin (hCG) which acts as immunomodulator and improves implantation by decidualization of the endometrial stromal cells, trophoblast invasion, proliferation of uterine natural killer cells, stimulation of endometrial angiogenesis, and maintenance of progesterone secretion by the corpus luteum. Aim: The aim of the study is to evaluate the effect of intrauterine hCG administration before IUI on CPR. Settings and Design: A prospective parallel randomized control study was done from September 2017 to February 2019. Materials and Methods: A total of 200 eligible women planned for IUI were randomly divided just before IUI into 2 groups. A computer-generated randomization list with block size of 10 with 1:1 allocation was used to randomize the patients. Experimental group received 0.5 ml containing 500 IU hCG, on the other hand control group received 0.5 ml of normal saline 2-3 min before IUI in single sitting. The main outcomes were CPR, miscarriage rate, and ongoing pregnancy rate. Statistical Analysis: It was performed using statistical software version SPSS 17.0. Results: Patient's demographic and baseline characteristics were comparable in both the groups. CPR in experimental group was significantly high compared to control group (26% vs. 9%, P = 0.002). Ongoing pregnancy rate was also significantly higher in experimental group (23%) compared to control group (7%) (P = 0.003). No significant difference in miscarriage rate was seen between the two groups. No cases of ectopic pregnancy, ovarian hyperstimulation syndrome, or multiple pregnancy were reported. Conclusion: Intrauterine hCG administration is a simple procedure that can be used to improve pregnancy outcome in IUI cycles. Clinical Trial Registration Number CTRI/2017/12/010729.